E-Book of Risk Management in High School Chemistry Laboratories as an Effort to Enhance Occupational Safety and Health - Saraswati, Regina; Sudiana, I Ketut; Suja, I Wayan (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Chemistry laboratory activities at the senior high school level are essential for developing students’ conceptual understanding but simultaneously pose significant occupational safety and health (OSH) risks when not supported by adequate safety literacy and systematic risk management. Despite this urgency, accessible and structured learning resources that explicitly address laboratory risk management in school contexts remain limited. This study aimed to develop an e-book on risk management for high school chemistry laboratories as an innovative digital resource to strengthen students’ safety awareness and support the implementation of OSH practices during chemistry practicums. Using a Research and Development approach with the 4D model, the e-book was designed, validated by experts, and tested for readability and practicality. The results indicate that the e-book achieved very high validity in terms of content, language, and media, was highly readable (95.6%), and demonstrated strong practicality for classroom use (82.5% by teachers and 96.8% by students). These findings suggest that the developed e-book is an effective and feasible digital learning resource that can contribute to fostering a stronger culture of safety and risk awareness in high school chemistry laboratories.